The Accounting of Accrual, Taxation and Payment of Yearly Vacation Leaves To Bussiness Enterprise Employees - О. YURCHENKO (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
Because the early vacation leave is a state guarantee of the constitutional right of an employee for his/her recreation, with the right for vacation leave ensured for employees of all business enterprises, both private and public, including the ones hired by entrepreneurs – physical persons, issues of accounting and payment of vacation leaves to business enterprise employees have the priority status in the payroll accounting. The correctness of calculated compensations, including vacation leaves, is a factor regulating the labor discipline in a business enterprise.  The article presents the author’s vision of the procedure of accrual, taxation and payment of the yearly vacation leave in a business to business enterprise employees. The types of vacation leaves fixed in the Labor Code of Ukraine are outlined; the duration of vacation leaves by employee category are shown; the need for monitoring the issues related with granting the yearly vacation leave, and the procedure of its accrual, taxation and payment are elaborated on; the phases of documenting the yearly vacation leave in a business enterprise are determined; the algorithm for calculating the yearly vacation leave is demonstrated. Recommendations on improvements in the documenting and recording of calculations of yearly vacation leave due to business enterprise employees are proposed, which are expected to enhance the recording functions of the payroll accountant and increase the quality of analytical information for decision-making purposes.